Rapid changes in heatwaves pose dual challenge in Eastern China and its adjacent seas - Yao, Yulong; Wang, Junjie; Zou, Xinqing (Frontiers in Marine Science, 2022)
This paper performs a comparative analysis of the spatiotemporal variations of the statistical characteristics of both atmospheric heatwaves over the land (AHWs) in eastern China and marine heatwaves (MHWs) in adjacent seas using a unified heatwave definition. The multi-year average total days and frequency of MHWs during 1982-2019 were 5 and 2 times higher than those of AHWs, respectively, while the mean intensities of AHWs and MHWs were unchanged. The future frequency and duration of AHWs will continue to increase, leading to a superimposed increase in AHW total days. The decreasing frequency and increasing duration of MHWs will result in nearly year-round MHWs from 2060. Under the control of high-pressure systems, clear skies dominate the summer weather conditions in eastern China and its adjacent seas, which will trigger heatwaves. Heatwaves in turn can release substantial ocean latent heat. Enhanced convection and heating will further drive a stronger anticyclone over the western North Pacific, leading to a stronger and more westward-extending western North Pacific subtropical high (WNPSH). Moreover, super El Niño can promote an anomalous WNPSH in decaying summer, which may cause more serious heatwaves. The multi-year average persons affected by AHWs (PAHWs) during 1982-2019 were larger in the North China Plain, Yangtze River Delta, and Sichuan Basin with the regional sum exceeding 3 million. The future maximum PAHWs under SSP2-4.5 and SSP5-8.5 scenarios will be 3.9 billion in 2076 and 4.7 billion in 2085, respectively. Marine ecosystems like artificial ranches and coral reefs will be more threatened by longer-lasting MHWs.